2014
DOI: 10.1021/la500402m
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Phase, Surface Tension-Based Fabrication Method for Generation of Tumor Millibeads

Abstract: Numerous methods have been developed for the fabrication of poly(ethylene glycol)-based hydrogel microstructures for drug-delivery and tissue-engineering applications. However, present methods focus on the fabrication of submicrometer scale hydrogel structures which have limited applications in creating larger tissue constructs, especially in recreating cancer tissue microenvironments. We aimed to establish a platform where cancer cells can be cultured in a three-dimensional (3D) environment, which closely rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 41 publications
(45 reference statements)
0
33
0
Order By: Relevance
“…However, cells located in the interior regions of the tumor tissue experience diffusional gradients of oxygen (leading to hypoxia) and nutrients (leading to accumulation of waste metabolites and acidic pH) . Previously, we have shown that MCF7 cells cultured within spheroidal PEGDA hydrogel millibeads (2 mm diameter) exhibit viable cell layers in the hydrogel periphery, but undergo significant cell death in the interior regions of the millibeads . In another study, cancer cells encapsulated within transglutaminase‐crosslinked gelatin hydrogels also displayed growth and morphological heterogeneity due to onset of hypoxia in the central regions of millimeter‐scale large hydrogel constructs .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, cells located in the interior regions of the tumor tissue experience diffusional gradients of oxygen (leading to hypoxia) and nutrients (leading to accumulation of waste metabolites and acidic pH) . Previously, we have shown that MCF7 cells cultured within spheroidal PEGDA hydrogel millibeads (2 mm diameter) exhibit viable cell layers in the hydrogel periphery, but undergo significant cell death in the interior regions of the millibeads . In another study, cancer cells encapsulated within transglutaminase‐crosslinked gelatin hydrogels also displayed growth and morphological heterogeneity due to onset of hypoxia in the central regions of millimeter‐scale large hydrogel constructs .…”
Section: Discussionmentioning
confidence: 91%
“…56,57 Previously, we have encapsulated MCF7 cells within PEGDA tumor millibeads (2 mm in diameter) at 60 3 10 6 cells/mL and observed the formation of a central region of dead cells and a peripheral rim of viable cells, representative of the necrotic core of native tumors. 11 In our experience, high encapsulation densities and dense cell colonies at the hydrogel edge are necessary to establish a mass transfer gradient from the hydrogel periphery to the hydrogel interior for constructs of these dimensions and thereby demonstrate locational tumor heterogeneity as described in Figure 10.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations